Volcanoes monitoring using Arduino and Simulink platforms (2017)
The monitoring of volcanic activity is a major concern in those countries with high degree of seismicity. The main drawback is the high cost of instrumentation required to monitor the behavior of volcanoes, which limits access to updated information that allows carrying out prevention activities. This work presents the implementation of the acquisition of two variables associated to volcanic monitoring, using an Arduino and the Simulink tool of Matlab.A tilt or movement meter was implemented, which allows measuring the deformations of the volcanic building and the possible jolts that could exist of its cone, among other applications. In the same way, a temperature meter with a heater-resistance PT100 was also implemented. The experimentation allowed verifying the functionality of both, the inclination and temperature meters, throwing satisfactory results and with adequate relative errors. This allows concluding that the use of Simulink for the programming of the Arduino allows both the simulation and evaluation of the models, directly on the Arduino board during the design process, with the advantages offered by this alternative in saving time and simplicity in the device programming.